Cement-based grouting material
By reasonably proportioning multiple components in cement-based grouting materials, a curing system with high compressive strength, good waterproofing performance and acid-base corrosion resistance is formed, the existing grouting materials have been solved, and the high-performance application and environmental protection of grouting materials in complex environments is achieved.
Patent Information
- Application Number
- CN202411675410.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-18
AI Technical Summary
The existing grouting materials have single performance, which is difficult to take into account strength, waterproof, acid-proof, alkali corrosion and durability, and their performance is degraded in environments with harsh permeability or chemical corrosion, and are not environmentally friendly.
Cement-based grouting material is used to form a curing system with high compressive strength, good waterproofing and acid-base corrosion resistance by reasonably proportioning composite cement, kaolin, silica powder, acrylic resin, methyl-bisacrylamide, water reducing agent, waterproofing agent and retarder, and at the same time ensures environmental protection.
It realizes the high-performance application of grouting materials in complex engineering environments, has the characteristics of excellent comprehensive performance, strong durability, environmental protection and harmlessness, and is suitable for a variety of complex geological conditions.
Smart Images

Figure BDA0005146880120000061 
Figure BDA0005146880120000071 
Figure BDA0005146880120000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grouting materials, in particular to a cement-based grouting material. Background Art
[0002] Grouting technology, as a widely used means of foundation reinforcement and waterproofing engineering, is centered on injecting specific slurry into underground structures or rock and soil media to fill cracks, enhance structural strength or prevent water leakage. The flow properties of the grouting slurry, its compatibility with the stratum, and its physical and chemical properties after solidification are directly related to the success of the grouting project. However, in actual engineering applications, grouting faces a complex and changeable geological environment, especially soft and permeable strata and complex hydrogeological conditions, which puts higher requirements on the performance of grouting materials.
[0003] At present, there are many types of grouting materials on the market, including but not limited to sodium silicate, cement-based, polyurethane, acrylate, and epoxy resin. Different materials have their specific application scenarios and advantages. Sodium silicate grouting materials perform well in filling small cracks due to their good fluidity and strong permeability; cement-based grouting materials are favored for their high strength and good durability after curing; polyurethane grouting materials, acrylate grouting materials, and epoxy resin grouting materials play an important role in reinforcement and waterproofing in complex environments due to their excellent adhesion and toughness. However, these grouting materials also have obvious shortcomings, such as single performance: most existing grouting materials can only meet a single specific demand, such as strength, waterproofing or corrosion resistance, and it is difficult to achieve comprehensive performance optimization in a single product. In addition, the performance of most grouting materials will drop significantly in harsh environments with high permeability or chemical corrosion, and problems such as reduced strength and failure of waterproofing will occur. In addition, the environmental protection issue of grouting materials is also an extremely important issue. The polyurethane, acrylate and epoxy resin grouting materials in the grouting materials may release harmful gases during the curing process, posing a potential threat to the environment and human health, and do not meet the requirements of green buildings and environmentally friendly construction.
[0004] In summary, the limitations of existing grouting materials restrict their application in complex engineering environments. Developing a new type of grouting material with comprehensive performance, environmental protection and strong durability has become a key issue that needs to be urgently solved in the current grouting technology field. Summary of the invention
[0005] The main purpose of the present invention is to provide a cement-based grouting material to solve the problem that the grouting material in the prior art has a single performance and cannot take into account multiple performances such as strength, waterproofness, acid and alkali corrosion resistance and durability, and cannot achieve green and environmental protection at the same time.
[0006] In order to solve the above problems, the present invention provides a cement-based grouting material, which comprises the following components in parts by weight: 30-60 parts of composite cement, 15-25 parts of kaolin, 10-20 parts of silica powder, 20-30 parts of acrylic resin, 8-13 parts of methylene bisacrylamide, 1-3 parts of water reducer, 3-10 parts of waterproofing agent and 0.5-1.5 parts of retarder; wherein the composite cement comprises silicate cement and sulphoaluminate cement.
[0007] Furthermore, the cement-based grouting material comprises the following components in parts by weight: 30-50 parts of composite cement, 15-25 parts of kaolin, 15-20 parts of silica powder, 20-30 parts of acrylic resin, 8-13 parts of methylene bisacrylamide, 2-3 parts of water reducer, 5-10 parts of waterproofing agent and 0.5-1.5 parts of retarder; preferably, the weight ratio of acrylic resin to methylene bisacrylamide is (2-3):1; preferably, the weight content of waterproofing agent in the cement-based grouting material is 5-8%.
[0008] Furthermore, the composite cement is a compound of silicate cement and sulphoaluminate cement in a weight ratio of (1-2):1.
[0009] Further, the cement-based grouting material includes the following components, measured in parts by weight: 27 parts of Portland cement, 18 parts of sulphoaluminate cement, 20 parts of kaolin, 15 parts of silica powder, 25 parts of acrylic resin, 10 parts of methylene bisacrylamide, 2 parts of water reducer, 7 parts of waterproofing agent, and 1 part of retarder; or, 18 parts of Portland cement, 12 parts of sulphoaluminate cement, 15 parts of kaolin, 20 parts of silica powder, 24 parts of acrylic resin, 8 parts of methylene bisacrylamide, 2 parts of water reducer, 7 parts of waterproofing agent, and 1.5 parts of retarder; or, 30 parts of Portland cement, 20 parts of sulphoaluminate cement, 25 parts of kaolin, 15 parts of silica powder, 26 parts of acrylic resin, 13 parts of methylene bisacrylamide, 3 parts of water reducer, 10 parts of waterproofing agent, and 0.5 part of retarder.
[0010] Furthermore, the particle size of silicate cement is less than 30 μm, and the strength grade of silicate cement is 32.5-52.5; preferably, the particle size of sulphoaluminate cement is less than 30 μm, and the strength grade of sulphoaluminate cement is 42.5-72.5.
[0011] Furthermore, the water reducing agent is one or more of lignin sulfonate, polycyclic aromatic salt and polycarboxylic acid.
[0012] Furthermore, the retarder is one or more of hydroxycarboxylic acid, hydroxycarboxylate, polyol and alcohol derivatives thereof, phosphate, borax and sodium fluorosilicate.
[0013] Furthermore, the waterproofing agent is one or more of polyisobutylene, natural latex and silicone oil.
[0014] Furthermore, the particle size of the silicon dioxide powder is 100 to 200 nm.
[0015] Furthermore, the particle size of kaolin is less than 30 μm.
[0016] The present invention provides a cement-based grouting material, which is based on silicate cement and sulphoaluminate cement, and is intended to achieve high compressive strength performance, high durability, and good waterproof performance during the use of the cement-based grouting material by controlling the reasonable ratio of composite cement and kaolin, silica powder, acrylic resin, methylene bisacrylamide, water reducer, waterproof agent, and retarder in the cement-based grouting material, while taking into account its green environmental protection. The cement-based grouting material can not only effectively fill and reinforce, improve structural strength, but also construct a waterproof gel layer, significantly enhance waterproof performance, and at the same time, the cement-based grouting material has a low additive content, is not easy to release harmful substances, meets the technical requirements of green environmental protection, is suitable for complex engineering environments, and has broad application prospects. DETAILED DESCRIPTION
[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0018] As mentioned in the background technology section, the existing cement-based grouting materials on the market have many problems. For example, the performance is single: most of them can only meet single specific requirements such as strength, waterproofness or acid and alkali corrosion resistance, and it is difficult to optimize the comprehensive performance in a single product. Poor durability: The performance of most cement-based grouting materials will drop significantly in harsh environments with high permeability or chemical corrosion, and there will be problems such as reduced strength and failure of waterproof performance. Not environmentally friendly: Polyurethane, acrylate, and epoxy resin cement-based grouting materials in cement-based grouting materials may release harmful gases during the curing process, posing a potential threat to the environment and human health, and do not meet the requirements of green buildings and environmentally friendly construction.
[0019] In order to solve the above problems, the present invention provides a cement-based grouting material, which comprises the following components in parts by weight: 30-60 parts of composite cement, 15-25 parts of kaolin, 10-20 parts of silica powder, 20-30 parts of acrylic resin, 8-13 parts of methylene bisacrylamide, 1-3 parts of water reducer, 3-10 parts of waterproofing agent and 0.5-1.5 parts of retarder; wherein the composite cement comprises silicate cement and sulphoaluminate cement.
[0020] The above-mentioned cement-based grouting material is based on silicate cement and sulphoaluminate cement. By adding kaolin, silica powder, acrylic resin, methylene bisacrylamide, water reducer, waterproofing agent and retarder, and by strictly controlling the addition ratio of each component within the above-mentioned range, the synergistic effect between the components can be fully exerted, so that the solidified system of the cement-based grouting material after curing not only has excellent compressive strength, good waterproofness, acid and alkali corrosion resistance and high durability, but the above-mentioned cement-based grouting material formula also has the characteristics of low additive content, which is in line with the concept of green environmental protection.
[0021] Specifically, the composite cement in the cement-based grouting material is silicate cement and sulphoaluminate cement. The cement curing process is achieved through hydration reaction. The compounding of these two cements can make full use of the advantages of the early strength of sulphoaluminate cement and the late strength of silicate cement, and improve the fluidity and durability of the cement-based grouting material. Kaolin and silica powder are fine fillers. Controlling the addition ratio of the above two substances in the cement-based grouting material within the above range can make the cement-based grouting material more easily penetrate into the fine cracks during use, enhance the filling and stability of the cement-based grouting material, and also help to reduce the shrinkage of the material after curing, and improve the density and strength of the cured material. In addition, silica powder can also react chemically with the hydration products in cement to generate silicate gel with more stable properties, further enhancing the waterproof performance and corrosion resistance of the cured material. At the same time, the waterproofing agent in the cement-based grouting material can act with the various components in the cement-based grouting material to better construct a waterproof system, so that the cement-based grouting material forms a waterproof layer in the cured system, effectively preventing the penetration of water, thereby protecting the structure from water damage. Adding water reducer and retarder to cement-based grouting material can make the cement-based grouting material have a suitable curing time when used. Controlling the addition ratio of water reducer and retarder within the above range can improve the fluidity of cement-based grouting material, improve the pumpability and injection performance of cement-based grouting material, and make the cement-based grouting material have enough time to flow and penetrate when injected into the formation or crack, which helps to improve the grouting effect and ensure that the cement-based grouting material can fully fill the target area.
[0022] Acrylic resin and methylene bisacrylamide are also added to the cement-based grouting material of the present invention, wherein the acrylic resin can significantly improve the fluidity, bonding force and crack resistance of the cement-based grouting material, and it can form an elastic film in the material system after the cement-based grouting material is cured, increase the toughness of the cement-based grouting material, effectively prevent the formation of cracks, and also provide additional waterproofing. Methylene bisacrylamide, as a highly efficient cross-linking agent, can promote the cross-linking reaction of acrylic resin in the cement-based grouting material, thereby accelerating the curing process and improving the strength and stability after curing. The addition ratio of the above two substances is controlled within the above range, which can improve the compressive strength and flexural strength of the cement-based grouting material after curing, and act together with components such as waterproofing agents to form a barrier waterproof gel layer in the cement-based grouting material, achieve a waterproof effect, and also hinder the penetration of corrosive media, improve its acid and alkali corrosion resistance and durability. In addition, acrylic resin also has the characteristics of low toxicity, which is in line with the concept of green environmental protection.
[0023] In summary, by controlling the various components and their addition ratios in the cement-based grouting material formula within the above range, the grouting effect of the cement-based grouting material can be effectively improved, so that the solidification system of the cement-based grouting material after solidification has excellent strength, waterproofness, acid and alkali corrosion resistance and high durability. At the same time, the cement-based grouting material of the present invention does not require harmful materials such as polyurethane, acrylate, epoxy resin, etc., and has good environmental protection.
[0024] In a preferred embodiment, the cement-based grouting material includes the following components by weight: 30-50 parts of composite cement, 15-25 parts of kaolin, 15-20 parts of silica powder, 20-30 parts of acrylic resin, 8-13 parts of methylene bisacrylamide, 2-3 parts of water reducer, 5-10 parts of waterproofing agent and 0.5-1.5 parts of retarder. Controlling the addition ratio of each component in the cement-based grouting material within the above range can further improve the strength, waterproofness and acid and alkali corrosion resistance of the solidified system after the slurry is solidified. Preferably, the weight ratio of acrylic resin and methylene bisacrylamide is (2-3): 1; controlling the addition ratio of acrylic resin and methylene bisacrylamide within the above range can make methylene bisacrylamide more effectively promote the cross-linking reaction of acrylic resin in cement-based grouting material, thereby further improving the compressive strength, stability, waterproofness and corrosion resistance of the solidified system after solidification. Preferably, the weight content of waterproofing agent in cement-based grouting material is 5-8%. By adding the waterproofing agent in the cement-based grouting material in the above-mentioned range, the cement-based grouting material can better construct a waterproof system during use, and the cured system after curing has better waterproof performance.
[0025] In a preferred embodiment, the composite cement is a compound of silicate cement and sulphoaluminate cement in a weight ratio of (1-2): 1. Controlling the addition ratio of silicate cement and sulphoaluminate cement in the composite cement within the above range can better coordinate the late strength of silicate cement and the early strength of sulphoaluminate cement, so that the cement-based grouting material has better compressive strength and durability after curing.
[0026] In a preferred embodiment, the cement-based grouting material comprises the following components, measured in parts by weight: 27 parts of Portland cement, 18 parts of sulphoaluminate cement, 20 parts of kaolin, 15 parts of silica powder, 25 parts of acrylic resin, 10 parts of methylene bisacrylamide, 2 parts of water reducer, 7 parts of waterproofing agent, and 1 part of retarder; or, 18 parts of Portland cement, 12 parts of sulphoaluminate cement, 15 parts of kaolin, 20 parts of silica powder, 24 parts of acrylic resin, 8 parts of methylene bisacrylamide, 2 parts of water reducer, 7 parts of waterproofing agent, and 1.5 parts of retarder; or, 30 parts of Portland cement, 20 parts of sulphoaluminate cement, 25 parts of kaolin, 15 parts of silica powder, 26 parts of acrylic resin, 13 parts of methylene bisacrylamide, 3 parts of water reducer, 10 parts of waterproofing agent, and 0.5 parts of retarder. By way of example but not limitation, controlling the addition ratio of each component in the cement-based grouting material within the above range can enable the various components to better exert their synergistic effects, further improving the compressive strength of the cement-based grouting material after curing, and making it have excellent waterproofness, corrosion resistance and high durability.
[0027] In a preferred embodiment, the particle size of silicate cement is less than 30 μm, and the strength grade of silicate cement is 32.5 to 52.5; preferably, the particle size of sulphoaluminate cement is less than 30 μm, and the strength grade of sulphoaluminate cement is 42.5 to 72.5. Controlling the particle size and strength grade of silicate cement and sulphoaluminate cement within the above range can further improve the high filling property and structural strength of cement-based grouting material, so that the cement-based grouting material has good applicability even under complex geological conditions.
[0028] By way of example but not limitation, the waterproofing agent is one or more of polyisobutylene, natural latex and silicone oil. The water reducing agent is one or more of lignin sulfonate, polycyclic aromatic salt and polycarboxylic acid. The lignin sulfonate includes but is not limited to calcium lignin sulfonate and sodium lignin sulfonate; the polycyclic aromatic salt includes but is not limited to naphthalene and naphthalene homologous sulfonates, formaldehyde condensed salts and amino sulfonates; the polycarboxylic acid includes but is not limited to macromolecular compounds with sulfonate, carboxylate, hydroxyl, ether bond and polyoxyethylene side chains, and high molecular surfactants with comb-like structures synthesized by free radical polymerization in aqueous solution. The retarder is one or more of hydroxycarboxylic acid, hydroxycarboxylate, polyol and its derivatives, phosphate, borax and sodium fluorosilicate. The hydroxycarboxylic acid includes but is not limited to gluconic acid, tartaric acid and citric acid; the hydroxycarboxylate includes but is not limited to sodium gluconate, sodium tartrate and sodium citrate; the polyol and its derivatives include but are not limited to glycerol and polyvinyl alcohol; the phosphate includes but is not limited to sodium pyrophosphate, sodium dipolyphosphate, sodium tripolyphosphate, potassium dihydrogen phosphate and sodium dihydrogen phosphate. The present invention does not particularly limit the specific types of water reducers, retarders and waterproofing agents. The above-mentioned specific types of water reducers, retarders and waterproofing agents are relatively common and have good effects when used in the cement-based grouting material described in the present invention.
[0029] In a preferred embodiment, the particle size of silica powder is 100-200nm, and the particle size of kaolin is less than 30μm. Silica powder and kaolin play a role in improving the permeability of cement-based grouting materials in gaps, enhancing the filling and stability of cement-based grouting materials, reducing the shrinkage of materials, and improving the density and strength after curing. Controlling the particle sizes of silica powder and kaolin within the above range can make the above effects better. In addition, silica powder with a smaller particle size is more conducive to chemical reaction with the hydration reaction products in cement to generate silicate gel, thereby enhancing the waterproof performance and corrosion resistance of the cement-based grouting material after curing.
[0030] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0031] Example 1
[0032] The components and addition proportions (by weight) of the cement-based grouting material are shown in Table 1, wherein the water reducer is calcium lignin sulfonate, the waterproofing agent is polyisobutylene, and the retarder is gluconic acid.
[0033] Table 1
[0034] Components Add ratio (portions) Component parameters Portland cement 18 Particle size <30μm, strength grade 32.5 Sulphoaluminate cement 12 Particle size <30μm, strength grade 42.5 Kaolin 15 Particle size <30μm Silica powder 10 Particle size: 100nm Acrylic resin 20 / Methylene Bisacrylamide 8 / Water reducing agent 1 / Waterproofing 3 / Retarder 0.5 /
[0035] Example 2
[0036] The components and addition proportions (by weight) of the cement-based grouting material are shown in Table 2, wherein the water reducer is naphthalenesulfonate, the waterproofing agent is natural latex, and the retarder is sodium tartrate.
[0037] Table 2
[0038] Components Add ratio (portions) Component parameters Portland cement 36 Particle size <30μm, strength grade 52.5 Sulphoaluminate cement 24 Particle size <30μm, strength grade 72.5 Kaolin 25 Particle size <30μm Silica powder 20 Particle size: 200nm Acrylic resin 30 / Methylene Bisacrylamide 13 / Water reducing agent 3 / Waterproofing 10 / Retarder 1.5 /
[0039] Example 3
[0040] The components and addition proportions (by weight) of the cement-based grouting material are shown in Table 3, wherein the water reducer is polycarboxylic acid, the waterproofing agent is silicone oil, and the retarder is propylene glycol.
[0041] Table 3
[0042]
[0043]
[0044] Example 4
[0045] The components and addition proportions (by weight) of the cement-based grouting material are shown in Table 4, wherein the water reducer is polycarboxylic acid, the waterproofing agent is silicone oil, and the retarder is sodium pyrophosphate.
[0046] Table 4
[0047] Components Add ratio (portions) Component parameters Portland cement 18 Particle size <30μm, strength grade 42.5 Sulphoaluminate cement 12 Particle size <30μm, strength grade 52.5 Kaolin 15 Particle size <30μm Silica powder 20 Particle size: 150nm Acrylic resin 24 / Methylene Bisacrylamide 8 / Water reducing agent 2 / Waterproofing 7 / Retarder 1.5 /
[0048] Example 5
[0049] The components and addition proportions (by weight) of the cement-based grouting material are shown in Table 5, wherein the water reducer is calcium lignin sulfonate, the waterproofing agent is silicone oil, and the retarder is sodium dipolyphosphate.
[0050] Table 5
[0051]
[0052]
[0053] Example 6
[0054] The components and addition proportions (by weight) of the cement-based grouting material are shown in Table 6, wherein the water reducer is calcium lignin sulfonate, the waterproofing agent is silicone oil, and the retarder is polyvinyl alcohol.
[0055] Table 6
[0056] Components Add ratio (portions) Component parameters Portland cement 20 Particle size <30μm, strength grade 42.5 Sulphoaluminate cement 10 Particle size <30μm, strength grade 52.5 Kaolin 15 Particle size <30μm Silica powder 15 Particle size: 150nm Acrylic resin 20 / Methylene Bisacrylamide 8 / Water reducing agent 2 / Waterproofing 5 / Retarder 0.5 /
[0057] Example 7
[0058] The components and addition proportions (by weight) of the cement-based grouting material are shown in Table 7, wherein the water reducer is calcium lignin sulfonate, the waterproofing agent is silicone oil, and the retarder is sodium citrate.
[0059] Table 7
[0060]
[0061]
[0062] Example 8
[0063] The components and addition proportions (by weight) of the cement-based grouting material are shown in Table 8, wherein the water reducer is naphthalenesulfonate, the waterproofing agent is natural latex, and the retarder is sodium tartrate.
[0064] Table 8
[0065] Components Add ratio (portions) Component parameters Portland cement 36 Particle size <30μm, strength grade 52.5 Sulphoaluminate cement 24 Particle size <30μm, strength grade 72.5 Kaolin 25 Particle size <30μm Silica powder 20 Particle size: 200nm Acrylic resin 20 / Methylene Bisacrylamide 10 / Water reducing agent 3 / Waterproofing 8 / Retarder 1.5 /
[0066] Example 9
[0067] The components and addition proportions (by weight) of the cement-based grouting material are shown in Table 9, wherein the water reducer is naphthalenesulfonate, the waterproofing agent is natural latex, and the retarder is sodium tartrate.
[0068] Table 9
[0069] Components Add ratio (portions) Component parameters Portland cement 30 Particle size <30μm, strength grade 52.5 Sulphoaluminate cement 20 Particle size <30μm, strength grade 72.5 Kaolin 15 Particle size <30μm Silica powder 15 Particle size: 200nm Acrylic resin 30 / Methylene Bisacrylamide 10 / Water reducing agent 1 / Waterproofing 10 / Retarder 1.5 /
[0070] Example 10
[0071] The components and addition proportions (by weight) of the cement-based grouting material are shown in Table 10, wherein the water reducer is calcium lignin sulfonate, the waterproofing agent is silicone oil, and the retarder is potassium dihydrogen phosphate.
[0072] Table 10
[0073] Components Add ratio (portions) Component parameters Portland cement 20 Particle size <30μm, strength grade 42.5 Sulphoaluminate cement 40 Particle size <30μm, strength grade 52.5 Kaolin 10 Particle size <30μm Silica powder 5 Particle size: 150nm Acrylic resin 15 / Methylene Bisacrylamide 20 / Water reducing agent 5 / Waterproofing 20 / Retarder 5 /
[0074] Comparative Example 1
[0075] The components and addition proportions (by weight) of the cement-based grouting material are shown in Table 11, wherein the water reducer is calcium lignin sulfonate, the waterproofing agent is polyisobutylene, and the retarder is sodium tartrate.
[0076] Table 11
[0077] Components Add ratio (portions) Component parameters Portland cement 18 Particle size <30μm, strength grade 32.5 Sulphoaluminate cement 12 Particle size <30μm, strength grade 42.5 Kaolin 15 Particle size <30μm Silica powder 10 Particle size: 100nm Methylene Bisacrylamide 8 / Water reducing agent 1 / Waterproofing 3 / Retarder 0.5 /
[0078] Comparative Example 2
[0079] The components and addition proportions (by weight) of the cement-based grouting material are shown in Table 12, wherein the water reducer is calcium lignin sulfonate, the waterproofing agent is polyisobutylene, and the retarder is sodium tartrate.
[0080] Table 12
[0081] Components Add ratio (portions) Component parameters Portland cement 18 Particle size <30μm, strength grade 32.5 Sulphoaluminate cement 12 Particle size <30μm, strength grade 42.5 Kaolin 15 Particle size <30μm Silica powder 10 Particle size: 100nm Acrylic resin 20 / Water reducing agent 1 / Waterproofing 3 / Retarder 0.5 /
[0082] Comparative Example 3
[0083] The components and addition proportions (by weight) of the cement-based grouting material are shown in Table 13, wherein the water reducer is calcium lignin sulfonate, the waterproofing agent is polyisobutylene, and the retarder is sodium tartrate.
[0084] Table 13
[0085] Components Add ratio (portions) Component parameters Portland cement 18 Particle size <30μm, strength grade 32.5 Sulphoaluminate cement 12 Particle size <30μm, strength grade 42.5 Kaolin 15 Particle size <30μm Silica powder 10 Particle size: 100nm Water reducing agent 1 / Waterproofing 3 / Retarder 0.5 /
[0086] The cement-based grouting materials in Examples 1 to 10 of the present invention and Comparative Examples 1 to 3 were prepared into mixed slurries according to a water-to-material ratio of 0.4 (i.e., 0.4 parts of water were added to every 1 part of cement-based grouting material dry material), and the density and viscosity thereof were tested after being stirred evenly. The mixed slurries obtained above were formed and cured in the same manner, and then the compressive strength, acid resistance, alkali resistance and water resistance thereof were tested respectively, and the test results are shown in Table 14. The specific test methods are as follows:
[0087] Density test method: Density test is carried out according to GB / T208-2014 "Determination method of cement density";
[0088] Viscosity test method: The viscosity test is carried out in accordance with GB / T43876-2024 "Method for Determination of Viscosity of Cement Paste"; use a mud hydrometer to measure according to the following steps: Prepare the mud sample: Pour the mud into the mud cup, make sure that the mud surface is flush with the cup mouth, and avoid bubbles. A funnel can be used to help inject the mud to ensure that the mud does not spill. Cover the cup lid tightly: Gently cover the cup lid, and the excess mud and air will be discharged from the small hole in the middle of the cup lid, or bubbles will emerge. Make sure that the cup lid is well sealed to avoid affecting the measurement results. Adjust the balance: Place the main blade of the lever on the main blade pad of the base, slowly move the weight, and observe the position of the bubble. When the bubble is in the center, it means that the lever is horizontal and you can read it. Reading: When the lever is horizontal, read the scale on the left side of the weight, which is the specific gravity of the mud. If you need to measure a specific gravity in a specific range, you can put the balance weight into the cylindrical barrel and measure it according to the above steps. Cleaning and maintenance: After use, wipe the barrel of the mud hydrometer and the parts stained with mud clean for next use. Make sure the instrument is clean to extend its service life.
[0089] Compressive strength test: The compressive strength is measured according to GB / T17671-2021 "Test method for strength of cement mortar";
[0090] Acid resistance test: The grouting material is molded with a standard mortar test mold, cured in a standard environment of a curing box for 28 days, the prepared test piece is placed in a water tank, 5% nitric acid (HNO3) solution is added to the test piece, soaked for 24 hours, the test piece is taken out, the surface is cleaned, and the weight of the test piece before and after soaking is measured. The acid resistance test result is: (test piece weight after test - test piece weight before test) / test piece weight before test × 100%;
[0091] Alkali resistance test: the grouting material is molded with a standard mortar test mold, cured in a standard environment of a curing box for 28 days, the prepared test piece is placed in a water tank, a 10% sodium hydroxide (NaOH) solution is added to the test piece, and the test piece is soaked for 24 hours, the test piece is taken out, the surface is cleaned, and the weight of the test piece before and after soaking is measured. The result of the alkali resistance test is: (weight of the test piece after the test - weight of the test piece before the test) / weight of the test piece before the test × 100%;
[0092] Waterproof test: The waterproof test is based on the standard JC / T 984-2011 "Polymer Cement Waterproof Mortar". The grouting material pure slurry test block is formed and the 28-day anti-seepage pressure of the test block is tested according to the standard method. It is qualified when the anti-seepage pressure is greater than 1.5MPa. The waterproofness can be evaluated according to the specific test values.
[0093] Explanation of the acid resistance test results and alkali resistance test results: when the test result is ≤5%, it means that the acid and alkali resistance are excellent; 5%<test result ≤10%, it means that the acid and alkali resistance are excellent; 10%<test result ≤15%, it means that the acid and alkali resistance are average; the test result>15%, it means that the acid and alkali resistance are unqualified. The acid and alkali resistance can be evaluated according to the specific values.
[0094] Table 14
[0095]
[0096]
[0097] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects: Examples 1 to 9 are cement-based grouting materials prepared by adopting the formula of the cement-based grouting material of the present invention and strictly controlling the addition ratio of each component. According to the results in Table 1, the density of the mixed slurry prepared by the above embodiments is higher and the viscosity is also higher. After it is formed and cured, the test results of its compressive strength, acid resistance, alkali resistance and waterproofness are also better. The characteristics of high density of the mixed slurry can reflect that the solidification system formed after its solidification not only has good compressive strength, but also has better porosity. The characteristics of greater viscosity of the mixed slurry can explain that an effective waterproof gel layer is constructed in the cement-based grouting material system, which can further improve the waterproof performance and acid and alkali corrosion resistance of the solidification system after solidification, so that it has good compressive strength, acid resistance, alkali resistance and waterproofness. It should be noted that the above effects are better when the addition ratio of each component in the cement-based grouting material is controlled within the preferred range.
[0098] The proportions of the various components in the cement-based grouting material in Example 10 are not within the range described in the present invention, and the density and viscosity of the prepared mixed slurry, as well as the compressive strength, acid resistance, alkali resistance and waterproofness of the solidified system formed after solidification are poor. In Comparative Examples 1 to 3, the cement-based grouting materials lack one or two of the components described in the present invention, and the above-mentioned effects are far different from those of the cement-based grouting materials in Examples 1 to 9 of the present invention.
[0099] In summary, the formula of the cement-based grouting material described in the present invention can achieve effective filling and reinforcement, improve structural strength, and have a good effect on improving the waterproof performance of the structure and the acid and alkali corrosion resistance and improving its durability. In addition, the cement-based grouting material described in the present invention also has the advantage of low additive content. While taking into account the overall performance, it can also meet the technical requirements of green environmental protection. In short, the cement-based grouting material described in the present invention is a cement-based grouting material with excellent comprehensive performance, which has a wide range of application prospects and has significant progressive significance.
[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A cement-based grouting material, characterized in that: The cement-based grouting material comprises the following components in parts by weight: 30-60 parts of composite cement, 15-25 parts of kaolin, 10-20 parts of silica powder, 20-30 parts of acrylic resin, 8-13 parts of methylene bisacrylamide, 1-3 parts of water reducer, 3-10 parts of waterproofing agent and 0.5-1.5 parts of retarder; wherein the composite cement comprises silicate cement and sulphoaluminate cement.
2. The cement-based grouting material according to claim 1, characterized in that: The cement-based grouting material comprises the following components by weight: 30-50 parts of the composite cement, 15-25 parts of the kaolin, 15-20 parts of the silica powder, 20-30 parts of the acrylic resin, 8-13 parts of the methylene bisacrylamide, 2-3 parts of the water reducer, 5-10 parts of the waterproofing agent and 0.5-1.5 parts of the retarder; Preferably, the weight ratio of the acrylic resin to the methylene bisacrylamide is (2-3):1; Preferably, the weight content of the waterproofing agent in the cement-based grouting material is 5-8%.
3. The cement-based grouting material according to claim 1, characterized in that: The composite cement is a compound of the silicate cement and the sulphoaluminate cement in a weight ratio of (1-2):
1.
4. The cement-based grouting material according to any one of claims 1 to 3, characterized in that: The cement-based grouting material comprises the following components by weight: 27 parts of silicate cement, 18 parts of sulphoaluminate cement, 20 parts of kaolin, 15 parts of silica powder, 25 parts of acrylic resin, 10 parts of methylene bisacrylamide, 2 parts of water reducer, 7 parts of waterproofing agent, and 1 part of retarder; or, 18 parts of silicate cement, 12 parts of sulphoaluminate cement, 15 parts of kaolin, 20 parts of silica powder, 24 parts of acrylic resin, 8 parts of methylene bisacrylamide, 2 parts of water reducer, 7 parts of waterproofing agent, and 1.5 parts of retarder; or 30 parts of the silicate cement, 20 parts of the sulphoaluminate cement, 25 parts of the kaolin, 15 parts of the silica powder, 26 parts of the acrylic resin, 13 parts of the methylene bisacrylamide, 3 parts of the water reducer, 10 parts of the waterproofing agent, and 0.5 parts of the retarder.
5. The cement-based grouting material according to any one of claims 1 to 3, characterized in that: The particle size of the silicate cement is less than 30 μm, and the strength grade of the silicate cement is 32.5 to 52.5; Preferably, the particle size of the sulphoaluminate cement is less than 30 μm, and the strength grade of the sulphoaluminate cement is 42.5-72.
5.
6. The cement-based grouting material according to any one of claims 1 to 3, characterized in that: The water reducing agent is one or more of lignin sulfonate, polycyclic aromatic salt and polycarboxylic acid.
7. The cement-based grouting material according to any one of claims 1 to 3, characterized in that: The retarder is one or more of hydroxycarboxylic acid, hydroxycarboxylate, polyol and its derivatives, phosphate, borax and sodium fluorosilicate.
8. The cement-based grouting material according to any one of claims 1 to 3, characterized in that: The waterproofing agent is one or more of polyisobutylene, natural latex and silicone oil.
9. The cement-based grouting material according to any one of claims 1 to 3, characterized in that: The particle size of the silicon dioxide powder is 100-200 nm.
10. The cement-based grouting material according to any one of claims 1 to 3, characterized in that: The particle size of the kaolin is less than 30 μm.